How to cater your agritourism enterprise to travelers: exploring differences in traveler demand in the western U.S. - Van Sandt, Anders, author; Thilmany, Dawn, author; Department of Agricultural and Resource Economics, Colorado State University, publisher (Colorado State University. Libraries, 2016)
This fact sheet concentrates on the demand for agritourism in the Western U.S. and how consumer interest and benefits vary by agritourism activities offered and the area the agritourism site is in. Several papers have looked at the demand for agritourism (e.g. Hill et al. 2014 and Carpio et al. 2008), but this study is more careful to disentangle demand across areas of the West and key activities. This could help an operator understand whether an agritourism enterprise would be a potentially successful diversification strategy, and also, how they may grow or adjust an existing agritourism business to take greater advantage of particular traveler preferences.
Keywords: agrotourism; customers; diversification; farmscape